Comparison of laser and piezo incisions to accelerate orthodontic tooth movement - A pilot rat model study - Yilanci, Hilal; Kara, Burcak; Ilhan Ramoglu, Sabri (Annals of Medical Research, 2021)
Aim: The aim of this study was to determine changes in bone structure after laser and piezo incisions evaluated with micro-computed tomography (micro-CT).Materials and Methods: Forty-eight adult male Sprague Dawley rats were randomly divided into 4 groups: no additional intervention to accelerate tooth movement (n=15), laser incision (n=15), piezocision (n=15), and control (n=3). These groups were divided into subgroups based on duration of applied force: 0, 3, 7, 14, 21, and 28 days. Piezo and laser incisions were made vertically on the mesial palatal side of the left maxillary molar without flap elevation. Tooth movement, bone volume, and bone mineral density were evaluated with micro-CT. P values less than 0.05 were considered statistically significant.Results: There were no significant differences in bone mineral density, bone volume, or amount of tooth movement between time points in any of the groups. The amount of tooth movement was significantly different between the groups at day 21.Conclusion: These findings provide some initial basic understanding of changes in the bone following tooth movement alone and with piezocision and laser incisions. Larger sample sizes are needed to better elucidate their effects.
Keywords: Er-YAG lasers; orthodontic tooth movement; piezosurgery; X-Ray microtomography